Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

On the change in bacterial size and magnetosome features for magnetospirillum magnetotacticum (MS-1) under high concentrations of zinc and nickel - Kundu, S.; Kale, A. A.; Banpurkar, Arun G.; Kulkarni, G. R.; Ogale, S. B. (Biomaterials, 2009)
The characteristic size, shape and specific alignment of magnetite crystals synthesized by magnetotactic bacteria is a highly coordinated process with precise control over magnetosome vesicle formation, uptake and transport of Fe, and magnetite biomineralization. Magnetosome membranes along with some specific membrane proteins regulate crystal nucleation and morphology of magnetite. Several previous works have indicated that the morphology of mature magnetite crystals is largely unaffected by environmental conditions, though some recent studies have shown the possibility of manipulation of the biomineralization process. In this study we have examined the effects of high concentrations of Zinc and Nickel on the growth of Magnetospirillum magnetotacticum (MS-1) and the corresponding magnetosome formation. Using various characterizations it is shown that the growth of the bacterial cells, as well as the size, shape and magnetosome chain alignment is significantly influenced in the presence of high concentrations of Zn or Ni. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biomineralization; magnetite; Magnetosome; Magnetospirillum magnetotacticum; Nickel; zinc

Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer

Effect of inter-particle interactions on the magnetic properties of magnetite nanoparticles after coating with dextran - Sreeja, V.; Joy, Pattayil Alias (International Journal of Nanotechnology, 2011)
Nanoparticles of magnetite (Fe3O4) are synthesised by a coprecipitation method and coated with the biocompatible polymer, dextran. The uncoated and dextran coated magnetite nanoparticles are characterised by powder X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and magnetic measurements. The magnetic properties of the uncoated and coated magnetite nanoparticles are compared to study the effect of inter-particle magnetic interactions on the magnetic characteristics. Absence of magnetic hysteresis at room temperature indicates the superparamagnetic nature of the two samples. Evidence for the effect of reduced inter-particle magnetic interactions is directly obtained from the field dependence of magnetisation at room temperature. The decreased superparamagnetic blocking temperature and the nature and shape of the field cooled magnetisation curve of the dextran coated sample further confirmed that the inter-particle magnetic interactions are completely suppressed after coating.
Keywords: dextran coating; magnetic interactions; magnetic properties; magnetite; Nanoparticles